An interview with Dr. Martin Lamb on research in English language learning and teaching - Berta Torras Vila (Universitat Autònoma de Barcelona, 2016)
The author interviewed Dr. Martin Lamb (University of Leeds, United Kingdom) at the School of Education in Leeds, about research on English language learning and teaching and about the main challenges that this field of research currently faces.